A STUDY ON GRAMMATICAL KNOWLEDGE OF THE SECOND YEAR STUDENTS OF MTs DARUL HIKMAH PEKANBARU - Wulandari, Sri; Aruan, Rumiri; M. Syarfi, M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research belongs to descriptive research which used quantitative approach. It aimed to find out the level of grammar knowledge of the second year students of MTs Darul Hikmah Pekanbaru. The population of this research was the second year students of the school, while the number of populations was 265 students. Thirty one of them were the samples and selecting by cluster sampling technique. To collect the data, completion test was used as the instrument with the total number of items was fourty questions. It consist of verb to be, modal, singular and plural, demonstrative adjective, degree of comparison and simple present tense. The result of research shows that the mean score of students in grammar knowledge was 70.26 and it categorized into good level, and the most difficult component is degree of comparison with the mean score 65, and the easiest aspects is in term of verb to be with the mean score 77. In brief, the second year students have good ability in grammatical knowledge that has been learned in odd semester.Key Words: Students’ Ability, Grammar, Knowledge